Fundamental principles of engineering nanometrology - Leach, R. K. (Micro & nano technologies., 2014)
Working at the nano-scale demands an understanding of the high-precision measurement techniques that make nanotechnology and advanced manufacturing possible. This new edition of Fundamental Principles of Engineering Nanometrology provides a road map and toolkit for metrologists engaging with the rigor of measurement and data analysis at the nano-scale, from the fundamentals of precision measurement, to different measurement and characterization techniques. This book is an essential guide for the emerging nanomanufacturing and nanofabrication sectors, where measurement and standardiza.